If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y + 9 = 15 Reorder the terms: 9 + 1y = 15 Solving 9 + 1y = 15 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 1y = 15 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = 15 + -9 1y = 15 + -9 Combine like terms: 15 + -9 = 6 1y = 6 Divide each side by '1'. y = 6 Simplifying y = 6
| 9=s/3-6 | | -24-3= | | 2x-9=7x-89 | | 10s-95=4s-23 | | 18=3(18)-36 | | y=3-5/2x | | 3z-36=z | | 80/2= | | 3b=10b-84 | | 2t+4+2t-3t=2+2 | | x^2-18x+26=-6 | | -2*0(0+2-5)+3(-5*0+2*2)+2(6*0+2-8)= | | 3a-69=a+13 | | 4v-51=v | | 10=4+2k | | 10v-51=v+57 | | 5(6x-1)+4(11-5x)-3(3x+3)=-6 | | 2q-79=q-28 | | 2s-4=s | | 8u-1=5u+14 | | 10c-20=c+34 | | s+3=2s | | 6+3g=18 | | 84=6(d+10) | | 5(m-73)=80 | | (5x+1.3y)+(2.9x-0.6y)= | | -19x+23x=44 | | 4*x+3=43 | | 1/3(2p-1) | | 7/42=49 | | 5(0)+y=2 | | 27-5p=14-4p |